Coaching psicopedagógico en el desarrollo de habilidades socioemocionales en estudiantes de básica superior - Moreira Tapia , Robert Oswaldo (2025)
This study analyzed how psycho-pedagogical coaching can influence the development of socio-emotional skills in students of higher basic. Many students were identified as having difficulties in recognizing and managing their emotions, making responsible decisions and resolving conflicts assertively, which affected their well-being and academic performance. With the objective of improving these competences, a psycho-pedagogical coaching system was designed focused on strengthening emotional intelligence, empathy and self-regulation, the research combined qualitative and quantitative methods, applying interviews, standardized observations and tests such as the Bar-On emotional intelligence test and the empathy scale, suggesting that while some students demonstrated a certain level of development in these areas, Many still had difficulty in expressing their emotions or working as a team. Based on these findings, a structured system of psycho-pedagogical coaching was proposed that includes strategies for emotional regulation, effective communication and conflict resolution. This proposal seeks to provide practical tools to improve the school life and well-being of students, promoting more integral learning. Its implementation in the school curriculum is recommended, as well as teacher training and involvement of families to ensure a positive impact on the socio-emotional development of students.